The Chronicler's "Vorlage", Kalimi verses Auld - Clancy, Frank (Scandinavian journal of the Old Testament, 2019)
Graeme Auld's argument of the "Two Houses" sharing the same vorlage is rejected by Isaac Kalimi. Kalimi insists that the Chronicler used the proto-Masoretic book of Kings as his source. However, there are a number of problems not addressed by Kalimi including chronological patterns and conflicting synchronisms. There is every reason to believe that the redacted proto-Masoretic book of Kings and the book of Chronicles shared the same vorlage as Auld has argued.